Vahdet-i Vücûd Düşüncesini Açıklamada Halı Sembolizmi ve Muhyiddin-i Rûmî’nin Temsîl-i Kālîçe İsimli Risâlesi / The Symbolism of the Rug (Qalicha) to Expound the Doctrine of the Unity of Being and Muhyiddin al-Rumi's treatise "Tamthil Qalicha" - Yücer, Hür Mahmut (Journal of History Culture and Art Research, 2017)
Abstract In the Islamic thought, Wahdat Wujud (The Unity of Being) is generally defined as a doctrine which discusses the transition of the real being (the absolute being) to the methaphorical (the relative) one, its formation and quality. By means of this doctrine, questions concerning the relations of Allah, the universe and human being are answered and many obscure issues found in the Holy Qur'an and the hadiths become intelligible. In the center of the doctrine of the Unity of Being occur the categories of being such as maratib al-wujud (the ranks of being), hadarat khamsa (the five presences) and tanazzulat sab'a (the seven condescensions). The categories of being have been long dealt with in a similar manner in almost every corner of the Islamic World through explanatory works like those in the form of sharh (commentary). In order to facilitate the comprehension of the subject in question a number of symbolisms such as seed and tree, point and letter, steam and ice, mirror and dream (shadow) have been utilised. The symbolism of the rug (qalicha) which is focused by the present study has not been studied or drawn attention to until today. Thus Muhyi's treatise, Tamthil Qalicha is quite compelling. This study firstly endeavors to elucidate the symbolism of the rug and then presents a Turkish transliteration of the said treatise of Muhyi, Tamthil Qalicha. Öz Vahdet-i vücûd, İslam düşüncesinde en genel anlamıyla hakîki varlıktan mecâziye geçişi, kılınış (ca’liyet) ve nasıllığı anlatan nazariyenin adıdır. Bu nazariye ile Allah-âlem-insan münasebeti hakkında sorular karşılıklarını bulurve Kur’ân-ı Kerîm ve hadislerde geçen birçok müteşabih konu anlaşılır hale gelir. Vahdet-i vücud nazariyesinin ana çatısını merâtibü’l-vücûd, hazerât-ı hams, tenezzülât-ı seb’a gibi farklı isimlerle ifade edilen varlık kategorileri oluşturur. Varlık mertebeleri tarih boyunca İslam dünyasının her bölgesinde benzer tarzda açıklanmaya çalışılmış ve üzerine şerhler yazılmıştır. Anlatının daha iyi kavranabilmesi için çekirdek-ağaç, nokta-harf, buhar-buz, ayna-hayal (gölge) gibi bir takım sembolik anlatım tarzları tercih edilmiştir. Bu çalışmanın konusunu teşkil eden halı sembolizmi/metaforu üzerine farklı şekillerde dikkat çekilmiş olsa da bu güne kadar herhangi bir çalışma yapılmamıştır. Bu konuda Muhyî’nin Temsîl-i Kālîçe isimli risalesi oldukça ilgi çekicidir. Çalışmamızın başında halı sembolizmini açıklamaya çalışacağız. Daha sonra Temsîl-i Kālîçe’nin günümüz Türkçesi ile yazımını vereceğiz.